KAJIAN PROBLEMATIKA DAN STRATEGI PENINGKATAN KETERAMPILAN MENULIS SISWA KELAS TINGGI SEKOLAH DASAR - Genio Firstchildlov Hesdevo; Melva Zainil; Inggria Kharisma; Annisa Olivia Memosa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Writing skills are essential language competencies for upper-grade elementary school students, as they contribute to the development of critical thinking, creativity, and written communication. However, various problems are still encountered in writing instruction, including limited vocabulary, inadequate mastery of language rules, low student motivation, and the use of less varied teaching strategies. This study aims to examine the problems faced by upper-grade elementary school students in writing and to identify effective strategies for improving these skills. The research employs a library research method, analyzing relevant scientific sources such as books, journal articles, and educational documents. Data were collected through literature search, selection, and critical analysis of sources related to writing skills. The findings indicate that effective strategies include the implementation of the process writing approach, project-based and collaborative learning models, the use of visual media and technology, and the provision of constructive and continuous feedback. This library study provides theoretical contributions as a foundation for developing more effective writing instruction practices in elementary schools. Keywords: writing skills, literacy, learning problems, improvement strategies.